The worst class trip ever - Barry, Dave (Disney/Hyperion, 2015)
"When the eighth grade civics class of Miami's Culver Middle School goes on a trip to Washington, D.C., Wyatt Palmer finds himself in deep trouble before the plane even lands because his best friend, Matt, has decided the men sitting behind them are terrorists and it is up to the boys to stop them"--Provided by publisher.